보육시설의 집단 크기에 따른 영아의 또래 및 교사와의 상호작용 - 권혜진(Hye Jin Kwon); 이순형(Soon Hyung Yi) (Korean Journal of child studies, 2001)
The purpose of this study was to analyze toddlers' verbal and nonverbal interaction with their peers and caregivers according to the class size of child care centers in Seoul. The subjects of this study were 20, two-year-old(M=32.5 month) toddlers with peers and caregivers from child care centers in different class sizes, but with same caregiver-toddler ratio. Verbal and nonverbal interactions were videotaped during one hour indoor free play per child in the center. According to the class size, the results were as follows : 1) Toddlers in the small class played more cooperatively with peers, and uttered more regulative or directive words than those in the large class. 2) Toddlers in the large class were more aggressive than those in the small class. 3) Caregivers in small class expressed more empathetic behaviors to a toddler than those in large class.